Aesthetic Transformations of Ogoh-Ogoh: From Conventional Giant Figures to Hybrid Myth–Popular Culture Characters - Suardana, I Wayan; Laba, I Nyoman; Jamnongsarn, Surasak (Jurnal Kajian Bali (Journal of Bali Studies), 2025)
Thousands of Ogoh-Ogoh (towering giant effigies) are paraded across Bali to welcome the arrival of the Saka New Year (Nyepi Day), which falls every March or April. This article examines the evolving aesthetics of these processions, tracing their shift from ritualistic giant figures meant to repel the destructive power of bhuta kala to contemporary hybrid mythic–popular forms that incorporate global pop-cultural icons and local socio-political characters. Employing qualitative methods such as visual ethnography, observation, and semiotic analysis, this study explores Ogoh-Ogoh production across Bali, where creative experimentation is especially vibrant. The findings reveal a significant aesthetic transformation driven by environmental regulations, competitive youth creativity, and the changing visual preferences of younger generations. Material innovations, including the use of LED lighting, have further intensified a performative orientation emphasizing spectacle and technical sophistication. Despite these shifts, ritual continuity endures, demonstrating that ogoh-ogoh remains a living, adaptive tradition in contemporary Balinese society.